The Occurrence and Bioactivities of Amaryllidaceae Alkaloids from Plants: A Taxonomy-Guided Genera-Wide Review - G. David Lin; Pinky Vishwakarma; Paul N. Smith; Rachel W. Li (Plants)
The distribution of Amaryllidaceae alkaloids, with a focus on their chemodiversity, has been reported previously, but not at a genera-wide diversity level. This review provides a comprehensive survey of the occurrence of Amaryllidaceae alkaloids across the genera of the Amaryllidaceae family. This survey is taxonomically guided by the National Center for Biotechnology Information (NCBI) Taxonomy Browser, with targeted keyword searches conducted in the Chemical Abstracts Service (CAS) SciFinder-n and PubMed. The family Amaryllidaceae comprises over 1214 species across three subfamilies: Agapanthoideae (1 genus, 5 species), Allioideae (3 genera plus 11 subgenera, 617 species), and Amaryllidoideae (58 genera plus 13 subgenera, 592 species). Amaryllidaceae alkaloids have been identified exclusively in 36 of the 58 genera and 6 of the 13 subgenera within the Amaryllidoideae subfamily. To date, more than 600 Amaryllidaceae alkaloids have been isolated, predominantly from this subfamily—hence the designation “Amaryllidaceae alkaloids”. These alkaloids display a wide spectrum of biological activities, including acetylcholinesterase inhibition, anti-inflammatory, antioxidant, antimicrobial, antidiabetic, and anticancer effects. A notable example is galanthamine (also known as galantamine), an FDA-approved drug marketed under the brand names Reminyl™ (Janssen Research Foundation, Beerse, Belgium, 2001) and Razadyne™ (Johnson & Johnson Pharmaceutical Research, New Brunswick, NJ, USA, 2004) for the treatment of mild to moderate Alzheimer’s disease, due to its potent acetylcholinesterase-inhibitory activity. Galanthamine has been isolated from species belonging to the genera Cyrtanthus, Galanthus, Leucojum, Lycoris, Narcissus, Ungernia, Chlidanthus, Crinum, Eucharis, Eustephia, Pancratium, and Phaedranassa. Lycorine is another widely distributed alkaloid found across multiple genera, and it has been extensively studied for its diverse bioactivities. Given the remarkable chemical diversity and bioactivity of Amaryllidaceae alkaloids, along with the many underexplored genera and species, further research into Amaryllidaceae species and their alkaloids is strongly warranted to support the discovery and development of novel therapeutic agents.